Kontribusi Guru Penggerak Dalam Meningkatkan Motivasi Pembelajaran PAI di Pulau Bangka: Jaryawati - Jaryawati Jaryawati (Magister Pendidikan Agama Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
A motivator is a teacher who mobilizes other teachers in independent learning to develop students' potential holistically. The mobilizing teacher also has the ability to develop innovative and creative learning strategies so that PAI learning becomes more intriguing and meaningful for students. Therefore, conducting research on the role of mobilizing teachers in enhancing PAI learning motivation is crucial. We anticipate that this research will aid in the advancement of Islamic education theory and practice in Indonesia, thereby enhancing the quality of Islamic education and bolstering students' learning motivation. In learning Islamic religious education, it is also necessary to promote the contribution of teachers to increase students' learning motivation. Teachers' contributions to enhancing PAI learning motivation on Bangka Island can lead to modifications in learning strategies, thereby significantly boosting student motivation. This type of research involves collecting data directly from informants, specifically PAI teachers who have taken on the role of mobilizing teachers at SDN 6 Riau Silip Bangka and SMAN 1 Koba Central Bangka. We employed a descriptive qualitative research method, utilizing both primary and secondary data. The findings demonstrated the role of activist teachers in enhancing PAI learning, as demonstrated by their shift in perspective towards student-centered learning and their ability to foster a positive learning environment, thereby boosting student motivation in PAI learning. This suggests that the more PAI teachers participate in the Mobilizing Teacher program, the greater the potential for significant changes in PAI learning. PAI teachers who have become teacher activists are more active in the learning community, sharing best practices with their colleagues and accepting opportunities to become principals. This allows them to easily create activity programs related to PAI learning and apply the knowledge they have gained during the teacher activist program